EFEKTIVITAS KEPATUHAN PELAPORAN SPT PPH TAHUNAN WAJIB PAJAK NON PEGAWAI DENGAN DITERAPKAN APLIKASI PAJAK ONLINE - Asyiami, Difa Nur; Andayani, Endro; Suryana, Ade (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
This study was conducted to determine the level of effectiveness of the Reporting of Annual Income Tax Returns for Non-Employee Taxpayers based on electronic filling at the Cakung Jakarta Pratama Tax Office. The basis for its implementation is the KUP Law and the Income Tax Law and other implementing regulations. The methodology used is qualitative by using observation and collecting data from people working in the company, literature review and interviews. Results: the effectiveness of Tax Compliance through e-Filing at the Cakung Jakarta Pratama Tax Office is quite effective in 2019 to 2022, in 2023 it is not effective. The obstacles are server down and new WPOPs do not understand online applications in reporting. Efforts that have been made with socialization and collaboration with the Tax Center at the University to participate in Tax Volunteers